PEMBERDAYAAN SEKOLAH DAN KOMITE SEKOLAH (STUDI EVALUASI KEBIJAKAN PADA PROGRAM BOS) DI KABUPATEN PACITAN - Suryanto, Sugeng (Universitas 17 Agustus 1945 Surabaya, 2016)
School Operational Aid (BOS) is a government policy through the Ministry of Educationand Culture, which is fully authorized its management to the schools by referring to theconditions set by the government. Schools with School Committee work together inutilizing the BOS funds to improve access and quality of education. With theimplementation of BOS policy on school, then it have need of evaluating the BOS policywhich this study discuss the empowerment of schools and the School Committee in themanagement of BOS. The problems of this research are about how: (1). The level of policyperformance of the BOS program; (2). The level of policy effectiveness of BOS program;(3). The level of policy outcome of the BOS program; (4). The policy impact of the BOSprogram. These four issues are analyzed in relation to empowerment of school and schoolcommittee. This research applied descriptive qualitative method, with the data in the formof descriptions of the activities, work systems or behaviors exist in Pacitan EducationDepartment, Schools and the School Committee recipient of BOS funds as the subject ofthe research. Data obtained by interview, observation and documentation studies. From thedata analysis and discussion, it is concluded as follows: First: The level of performance ofthe BOS policy have achieved the objectives which the BOS has been targeted to help thepoor students and ease the burden of other students; Second: The level of efficiencyindicates that with the lack of BOS funds schools can still carry out activities to reach thestandard results; Third: The level of outcomes have succeeded in increasing APK, controlfor APS, graduates proceed to a higher level, the BOS fund management transparent andaccountable, the increase of parents participation in helping schools, results of NilaiEbtanas Murni (NEM) increases, an increasing number of schools are accredited B;Fourth: The impact of policy on the BOS program, among others, the increase in theHuman Development Index (HDI), the increase in students passing the national exam andan increase in per capita income. Empowerment Schools and School Committee berealized where the school and the school committee has been undergoing development,strengthening the potential / power and independence.keywords : Empowerment, School and School Committee, Policy on the BOS program.